1996
DOI: 10.1074/jbc.271.18.10583
|View full text |Cite
|
Sign up to set email alerts
|

The Fyn Tyrosine Kinase Binds Irs-1 and Forms a Distinct Signaling Complex during Insulin Stimulation

Abstract: Irs-proteins link the receptors for insulin/IGF-1, growth hormones, and several interleukins and interferons to signaling proteins that contain Src homology-2 (SH2). To identify new Irs-1-binding proteins, we screened a mouse embryo expression library with recombinant [32P]Irs-1, which revealed a specific association between p59fyn and Irs-1. The SH2 domain in p59fyn bound to phosphorylated Tyr895 and Tyr1172, which are located in YXX(L/I) motifs. Mutation of p59fyn at the COOH-terminal tyrosine phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 44 publications
0
81
0
2
Order By: Relevance
“…This structure is very similar to the one exhibited by the Insulin Receptor Substrate-1 (IRS-1), a p185 kDa prominent cytoplasmic substrate of the InsulinReceptor (IR), Insulin like Growth Factor-Receptor (IGF-1R) and several cytokine receptors including interleukin (IL)-4 and IL-13 receptors (Schnyder et al, 1996). IRS-1 was found to form multimolecular complexes with the regulatory subunit of PI 3-kinase (Backer et al, 1993), SH-PTP2 (Kuhne et al, 1994), Nck (Lee et al, 1993), Grb2 (Pruett et al, 1995) and Fyn (Sun et al, 1996). Even though c-Cbl has also been shown to associate with a variety of transduction proteins, data supporting the formation of multimolecular complexes analogous to those observed with IRS-1 remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…This structure is very similar to the one exhibited by the Insulin Receptor Substrate-1 (IRS-1), a p185 kDa prominent cytoplasmic substrate of the InsulinReceptor (IR), Insulin like Growth Factor-Receptor (IGF-1R) and several cytokine receptors including interleukin (IL)-4 and IL-13 receptors (Schnyder et al, 1996). IRS-1 was found to form multimolecular complexes with the regulatory subunit of PI 3-kinase (Backer et al, 1993), SH-PTP2 (Kuhne et al, 1994), Nck (Lee et al, 1993), Grb2 (Pruett et al, 1995) and Fyn (Sun et al, 1996). Even though c-Cbl has also been shown to associate with a variety of transduction proteins, data supporting the formation of multimolecular complexes analogous to those observed with IRS-1 remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Although the well characterized insulin receptor substrates IRS-1/-2 and Shc emerged as potential candidates (54,55), none fulfilled all of these requirements. In contrast, the proto-oncogene product c-Cbl shares many properties with this presumed substrate protein.…”
Section: Discussionmentioning
confidence: 99%
“…In current studies, we (unpublished) have found that PKCε is also tyrosine phosphorylated and activated in response to insulin. Src tyrosine kinase has been shown to be involved in insulin and other growth factor signaling in several cell types, including skeletal muscle [52][53][54][55][56][57][58][59][60][42][43][44][45][46][47][48][49]. Moreover, in the case of PKCs α and δ, insulin-induced tyrosine phosphorylation is apparently mediated by the Src family of tyrosine kinases, if not Src tyrosine kinase itself ( [31] and unpublished).…”
Section: Mechanisms Of Activationmentioning
confidence: 99%
“…Equally not surprising were findings that PKCα expressed in cells co-expressing either IR or IRS1 (3T3ir, HEK293, COSIR) induced their phosphorylation. Thus, the idea has developed and persisted that PKCα might in fact play a role in development of insulin resistance [64][65][66][67][68][69][54][55][56][57][58]. Nonetheless, a role in insulin-induced effects has not been verified.…”
Section: Conventional Pkc Isoforms Pkcαmentioning
confidence: 99%